Macro Economics - Olivier Blanchard; BLANCHARD (Olivier) (Noida Pearson, 2023)
In Macroeconomics, Blanchard presents a unified, global view of macroeconomics, enabling students to see the connections between goods markets, financial markets, and labor markets worldwide. Organized into two parts, the text contains a core section that focuses on short-, medium-, and long-run markets and three major extensions that offer more in-depth coverage of the issues at hand. From the major economic crisis and monetary policy in the United States, to the problems of the Euro area and growth in China, the text helps students make sense not only of current macroeconomic events but also of events that may unfold in the future.Distinguished Authorship. Olivier Blanchard is one of Pearson$1 (Bs most notable economics authors and brings his years of experience and research of macroeconomic issues, including time as the chief economist at the International Monetary Fund, to the text. Comprehensive coverage of current events. Current macroeconomic events (such as Changes in the U.S. Natural Rate of Unemployment since 1990) are integrated into each chapter of the book within the text and detailed boxes. Each box shows students how they can use what they$1 (Bve learned to get an understanding of economics in the real world. Implications of the Equilibrium Model. Blanchard offers a unique, underlying model that shows the implications of equilibrium in three sets of markets: the goods market, the financial market, and the labor market, helping students understand the impact of equilibrium.s
Keywords: Financial Markets; Labor Market; Fiscal Policy; Unemployment